Tracking evolutionary paths in colonizing events temporal changes in life-history traits, microsatellites and inversions in Drosophila subobscura - Santos, Josiane (2016)
Tese de doutoramento, Biologia (Biologia Evolutiva), Universidade de Lisboa, Faculdade de Ciências, 2016